Base pressure studies from over expanded nozzle for area ratio 2.56 - Baig, Maughal Ahmed Al; Khan, Sher Afghan; Rathakrishnan, E. (Radiance Research Academy (Regd.), 2012)
The present paper aims at study of variations in base pressure at different levels of over expansion of jet in a suddenly expanded axi-symmetric duct. The results of an experimental investigation carried out at two different fixed levels of Over Expansion namely 0.277 and 0.56 are compared. The area ratio of the present study is 2.56. The jet Mach numbers at the entry to the suddenly expanded duct, studied are 2.2 and 2.58. The length-to-diameter ratio of the suddenly expanded duct is varied from 10 to 1. Active control in the form of four micro jets of 1mm orifice diameter located at 900 intervals along a pitch circle diameter of 1.3 times the nozzle exit diameter in the base region are employed. In addition to base pressure, wall pressure field along the duct is also studied. From the present studies it is found that at a high level of over expansion micro jets are marginally effective. It is also found from wall pressure studies that the micro jets do not disturb the flow field in the enlarged duct.